2020
DOI: 10.1371/journal.pgen.1008757
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional crosstalk between Hypoxia-Inducible Factor and glucocorticoid signalling in zebrafish larvae

Abstract: In the last decades in vitro studies highlighted the potential for crosstalk between Hypoxia-Inducible Factor-(HIF) and glucocorticoid-(GC) signalling pathways. However, how this interplay precisely occurs in vivo is still debated. Here, we use zebrafish larvae (Danio rerio) to elucidate how and to what degree hypoxic signalling affects the endogenous glucocorticoid pathway and vice versa, in vivo. Firstly, our results demonstrate that in the presence of upregulated HIF signalling, both glucocorticoid receptor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 84 publications
1
17
0
1
Order By: Relevance
“…Many other pathways were impacted by VitE deficiency, of note is collagen remodeling. egln3 , expressed in the neural plate in 12 hpf zebrafish embryos [ 32 ], is a hypoxia inducible factor (HIF) target and regulates the expression of collagen remodeling genes p4ha1b , plod1a and col1a1b [ 49 , 50 ]. VitE radicals produced as a result of lipid peroxidation reactions are chemically reduced by ascorbic acid (Vitamin C (VitC)), thereby depleting this critical antioxidant micronutrient [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many other pathways were impacted by VitE deficiency, of note is collagen remodeling. egln3 , expressed in the neural plate in 12 hpf zebrafish embryos [ 32 ], is a hypoxia inducible factor (HIF) target and regulates the expression of collagen remodeling genes p4ha1b , plod1a and col1a1b [ 49 , 50 ]. VitE radicals produced as a result of lipid peroxidation reactions are chemically reduced by ascorbic acid (Vitamin C (VitC)), thereby depleting this critical antioxidant micronutrient [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are confirmed by Marchi et al They have also demonstrated the repression of GR activity and its reduced responsiveness to exogenous GCs when HIF protein levels are upregulated in vhl -/zebrafish. Furthermore, cortisol levels were also reduced suggesting that HIF signalling can act both at the level of the hypothalamus by inhibiting Pomc expression and intracellularly by blocking the transcriptional activity of GR itself (82). A recent…”
Section: The In Vivo Crosstalk Between Hif and Gr And Its Role In Inflammationmentioning
confidence: 98%
“…GCs stabilize HIF via pVHL degradation HIF represses GR activity and the GR response to exogenous GCs (e.g. BME) in vhl -/zebrafish larvae (81,82) Cortisol levels are reduced by HIF due to repression of POMC expression and intracellular blocking the transcriptional activity of GR GCs in AMS Prophylactic effect of GCs when ascending to high altitude Administration of GCs (DEX and prednisolone) prior to ascending to high altitude reduces the symptoms of AMS (suppresses inflammatory pathways, reduces vascular permeability and vasoconstriction, improves arterial oxygenation and induces a better antioxidant-oxidant balance) (83-88)…”
Section: In Vivomentioning
confidence: 99%
“…High levels of hypoxia and HIF‐1α are associated with many of these conditions, including asthma, COPD, rheumatoid arthritis (RA), colitis and atherosclerosis [31–34]. Furthermore, HIF signalling interplays with key inflammatory signalling pathways, including glucocorticoids, mTOR and arachidonic acid [35–37].…”
Section: Dampening Hif In Chronic Inflammationmentioning
confidence: 99%